2019
DOI: 10.3389/fneur.2019.00792
|View full text |Cite
|
Sign up to set email alerts
|

What Comes First: Return to School or Return to Activity for Youth After Concussion? Maybe We Don't Have to Choose

Abstract: Objectives: Return to School (RTS) and Return to Activity/Play (RTA) protocols are important in concussion management. Minimal evidence exists as to sequence and whether progression can occur simultaneously. Experts recommend that children/youth fully return to school before beginning RTA protocols. This study investigates recovery trajectories of children/youth while following RTA and RTS protocols simultaneously, with the following objectives: (1) to compare rates and patterns of progression throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(50 citation statements)
references
References 44 publications
0
50
0
Order By: Relevance
“…Recent evidence recommends that youth progress through the initial stages of RTA and RTS protocols simultaneously, but the priority should be on their complete and successful RTS before returning to full contact sport 34. CanChild Pediatric Concussion Guidelines now recommend that children complete stages 1–3 of the RTA and RTS protocols together and then fully RTS before revisiting the last stages of the RTA protocol 34…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence recommends that youth progress through the initial stages of RTA and RTS protocols simultaneously, but the priority should be on their complete and successful RTS before returning to full contact sport 34. CanChild Pediatric Concussion Guidelines now recommend that children complete stages 1–3 of the RTA and RTS protocols together and then fully RTS before revisiting the last stages of the RTA protocol 34…”
Section: Discussionmentioning
confidence: 99%
“…Further evidence for the shortened rest period comes from parents in the Back to Play study, who reported the greatest difficulties with the rest period, given the extensive restrictions associated with this stage. 11 The recent adherence study confirmed that the lowest rates of compliance corresponded to Stages 1 and 2, suggesting that the recommendations for these stages needed to be adapted to make them more realistic and achievable, allowing children to return to their regular activities gradually and safely. 14 Research supports these findings, with 2 studies demonstrating that nearly half (40% to 48%) of concussed participants completed RTA and/or RTS prematurely.…”
Section: Discussionmentioning
confidence: 98%
“…Data collected from the aforementioned longitudinal study by DeMatteo et al 11 also examined adherence to the 2015 protocols 4,5 in individuals with concussion aged 5 to 18 years. 14 Both RTA and RTS protocols prescribe/recommend a certain level of time or activity intensity for each stage, increasing accordingly.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations